Pengaruh Pemberian Latihan Mengontrol Halusinasi terhadap Kemampuan Keluarga dalam Merawat Pasien Halusinasi - Meizela, Era (Jurnal Vokasi Keperawatan (JVK), 2023)
Hallucinations have a big impact on patients so they cannot control themselves, the family is the main support for the patient, one of the efforts to improve the ability of the family to treat hallucination patients is to provide hallucination control exercises with video demonstrations of how to control hallucinations.This study aims to determine the effect of providing hallucination control exercises on the ability of families to treat hallucinatory patients.This research is a quantitative research with a quasi experimental approach, taking samples using a purposive sampling technique which were divided into 2 groups of 17 experimental groups and 17 control groups. The measuring tool uses questionnaires that have been tested for validity and reliability and a video demonstration of exercises to control hallucinations. Data analysis uses the Wilcoxon test.The ability of the families of the experimenters in the pretest were mostly in the sufficient category of 14 people (82.4%),While the results of the pretest in the control group were all in the sufficient category with 17 people (100%).  After giving hallucination control exercises and conducting post tests in the experimental group, most of them were in the good category, 10 people (58.8%). While the control group in the post test obtained almost all results in the sufficient category of 15 people (88.2%). There is an effect of providing training to control hallucinations on the family's ability to treat hallucinatory patients with a pvalue of 0.003 (<0.05).Providing hallucination control exercises can improve the ability of families to treat hallucinatory patients.